Prenatal maternal mental health and fetal growth restriction: a systematic review. (17th March 2016) - Lewis, A. J.; Austin, E.; Galbally, M.
Abstract : Maternal mental disorders during pregnancy are associated with a range of adverse health outcomes for offspring. This systematic review examines studies reporting on the relationship between maternal depression, anxiety or stress during pregnancy and fetal growth measured during pregnancy using ultrasound biometry. A systematic search of PsycINFO, Medline, Scopus, Web of Science and Embase was conducted and 1575 records were identified, with nine studies meeting inclusion criteria gathering data from over 7000 participants. All studies measured depression, six examined anxiety and depression, and five examined all three exposures. The majority measured symptoms rather than clinically diagnosable disorder. Studies consistently reported significant associations between maternal mental health, particularly anxiety symptoms, and reduced fetal head growth. Other fetal growth parameters showed inconsistent findings. A number of studies suggest that cortisol dysregulation associated with maternal mental health may play a role in fetal growth restriction. However, heterogeneity in the timing of growth measurement, assessment measures used for mental health and inconsistencies in adjustment for confounders, limits the synthesis and interpretation of findings. Future studies should consider differences in the timing, intensity and duration of mental health symptoms over pregnancy and should employ diagnostic assessment of mental disorders. Fetal growth should be repeatedly measured and further work is needed to establish the biological mechanisms involved.